BLOCKCHAIN; POSSIBLE APPLICATION IN BANKING SECTOR A SYSTEMATIC REVIEW OF OPPORTUNITIES AND CHALLENGES - IBRAHIM, OMAR HAMID (Journal of Duhok University, 2023)
Innovative technologies are game-changing in the financial sector. The new-born technology (blockchain) is promising to change the entire banking system, despite various benefits, critical obstacles still stand. In addition, with an overview of major opportunities and challenges, this study aims to conduct a comparison between theoretical literature and practical literature to point out a contradiction if it exists. More than 130 references (paper studies and links) which were conducted by cryptography and technology experts, academics, financial institutions, and other sectors were used to achieve study aims. A systematic approach conducted to accomplish study objectives; we analyzed results and different point of views on blockchain application in banking globally. The study concluded that blockchain itself may hold strengths and weaknesses in a single aspect such as efficiency and security, while no contradictions were observed between the results on the ground and the theoretical literature. The vast majority of references indicate that blockchain will be the next banking system, which may change the legacy of banking. As it stands, the current blockchain-based applications are capable of operating in individual services, specifically in payment systems and cost operations. Financial companies which provide similar services can take advantage of this technology, especially in cross-border transfers, and this will retract a large share of bank profits in case this technology is not adopted. After all, a full adoption needs more improvement in projects and applications based on this technology.